2009
DOI: 10.1177/1350506809341512
|View full text |Cite
|
Sign up to set email alerts
|

Educational level and changes in health across Europe: longitudinal results from SHARE

Abstract: We use cross-national, longitudinal data to explore the impact of educational level on changes in health outcomes among Europeans aged over 50. Our analyses are performed separately for Northern, Western and Southern Europe, as these regions broadly represent different welfare state regimes. We find that low education is associated with higher incident events -over a two-year period -of poor health, chronic diseases and disability, but it is less consistently associated with new events of long-standing illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
60
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 39 publications
7
60
0
5
Order By: Relevance
“…To this end, we used five different binary indicators of health, taken from the second wave of SHARE and widely used in recent publications (e.g. Avendano et al, 2009): Poor self-perceived health (less than good), scoring high on depressive symptoms (more than three symptoms on the EURO-D-scale), diagnosed chronic diseases (two or more), self-reported symptoms (two or more), and a measure of functional limitation (at least one ADL or IADL limitation). To study associations between quality of work and early retirement (our second research question), we created a binary indicator measuring whether or not respondents were employed at the age of 60 (for all respondents aged 60 or older).…”
Section: Measuring Quality Of Work In Sharelifementioning
confidence: 99%
“…To this end, we used five different binary indicators of health, taken from the second wave of SHARE and widely used in recent publications (e.g. Avendano et al, 2009): Poor self-perceived health (less than good), scoring high on depressive symptoms (more than three symptoms on the EURO-D-scale), diagnosed chronic diseases (two or more), self-reported symptoms (two or more), and a measure of functional limitation (at least one ADL or IADL limitation). To study associations between quality of work and early retirement (our second research question), we created a binary indicator measuring whether or not respondents were employed at the age of 60 (for all respondents aged 60 or older).…”
Section: Measuring Quality Of Work In Sharelifementioning
confidence: 99%
“…Diese zeigen unter anderem, dass Personen mit niedriger Bildung im höheren Lebensalter ihren allgemeinen Gesundheitszustand häufi-ger als weniger gut einschätzen im Vergleich zu Personen mit höherer Bildung (Avendano et al 2005). Außerdem haben sie ein höheres Risiko für neuauftretende Gesundheitsprobleme und Funktionseinschränkungen im Altersverlauf (Avendano et al 2009). Besondere Beachtung verdient eine Auswertung der SHARE-Daten aus den Jahren 2004 und 2007, die Längsschnittdaten aus elf Ländern nutzt und der Frage nachgeht, ob sich gesundheitliche Unterschiede zwischen verschiedenen Bildungsgruppen im Alter vergrößern, verringern oder ob sie konstant bleiben.…”
Section: Internationaler Forschungsstandunclassified
“…Minicuci et al (2004) argued in a somewhat similar manner, pointing to marked differences in educational status between northern and southern European countries, which translate into differences in occupational and economic status, which are themselves determinants for health outcomes, and which are also related to individual lifestyle, health care utilization, and risk behavior. Avendano et al (2009) emphasized that, for southern European countries, the association of socioeconomic status and education level with health status is especially strong, leading to less favorable results in the south. He concluded that, because there is less variation in these determinants in northern and western Europe, health inequalities are smaller in these countries than in the southern countries.…”
Section: State Of Research: Health Inequalitiesmentioning
confidence: 99%